FOOD ALLERGY PREVENTION IN INFANCY - S.G. Makarova; T.E. Borovik; I.M. Guseva; G.V. Yatsyk; O.L. Lukoyanova ("Paediatrician" Publishers LLC, 2006)
The article deals with new data about food tolerance induction among the children, belonging to the high risk groups disposed to atopy. Authors show the role of gut microflora in formation of child immune system, effect of breast feeding on activation of local immune response, growth stimulation of bifid bacteria and lactic acid bacilli. The present work gives the randomized research findings, which confirm the effectiveness of prolonged breast feeding, use of highly or partially hydrolyzed mixtures and timely introduction of supplemental feeding in food allergy prevention. Key words: prevention, food allergy, children, breast feeding, hypo allergic mixtures, milk protein hydrolysates, supplemental feeding, gut microflora, probiotics.